LNG Markets: the great reconfiguration - Bassam Fattouh; Howard Rogers; Jonathan Stern (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2016)
The LNG market has seen dramatic shifts in its underlying fundamentals since the mid 2000s. The roller-coaster of pricing, the rise of LNG spot and short term trading and the emergence of the US as a source of 'destination flexible' supply are just some of the many dimensions of the industry which appear in a state of flux, not least due to the imminent arrival of new substantial supply from projects in Australia and the US. In September 2016 OIES and KAPSARC published 'LNG Markets in Transition – The Great Reconfiguration'. This Issue of the Oxford Energy Forum comprises articles from several of the book chapter authors and the editor who provide summaries of their key findings.
Keywords: 330